Recent revolutions in astronomy - Kelsey, Larry; Hoff, Darrel B. (New York : F. Watts, 1987)
Discusses how recent innovations such as the new telescopes are affe cting the study of astronomy, our understanding of the universe, and th e search for new galaxies and the origins of life.
Includes index.
Includes Bibliographical References (p. 124).
Keywords: Astronomy -- Juvenile literature; Astronomy. -- Juvenile literature; Outer space -- Exploration